(untitled) (American Journal of Islam and Society, 2001)
The term “postmodernity” perhaps owes its very popularity to the fact that it is notoriously difficult to define. It often means all things to all people, and by its very orientation, is critical of any attempts to offer blanket definitions. Nevertheless, we may discern three broad orientations that define postmodernity: 1. It involves an “incredulity toward metanarratives.”* In other words, it repudiates the modernist view thd individual actions can be explained through universal laws. 2. It focuses on the crisis of repre entation.I n other words, it is critical of the power vested in any subjectivity to represent the reality of another. 3. It problematizes the issue of subject and author? For example, it would question the claim made by this journal that it is a more ‘official’ interpreter of Islamic thought than some others: a claim this joumal may seek to advance on the basis of its institutional power. This somewhat arbitrary set of attributes associated with postmodernity may seem quite innocuous at first reading. But postmodernity (or its now emerging normative arm, postmodernism) is evidently much more than that, as its adherents and critics have pointed out. It has been associated with a lot of other phenomena. For instance, in the economic realm, we have the notion of post-Fordism, a situation where the precepts of mass production are being overturned. Based on computer-aided manufacture, a rapidly heterogenizing consumer demand, and the emergence of newer forms of commerce (such as Ecommerce over the internet), a new industrial paradigm is emerging.5 At the same time, we have the phenomenon of post-nationalism, where the sovereignty of nations is being threatened by the emergence of supranational forms of governance such as multinational corporations and the WT0.6 However, the issue that ...